Patterns for Success in the Adoption and Execution of Feature‐based Product Line Engineering: A Report from Practitioners. Issue 1 (30th September 2020) - Gregg, Susan P.; Hartley, David; McAfee, Morgan; Pitz, Randy; Teaff, James; Clements, Paul
Abstract: Systems and Software Product Line Engineering (PLE) is a general approach to engineer a portfolio of related products in an efficient manner, taking advantage of the products' similarities while respecting and managing their differences. The approach manages a product portfolio as a single entity, as opposed to a multitude of separate products. Numerous resources describe the organizational benefits associated with incorporating PLE techniques and tools. Feature‐based System and Software Product Line Engineering is a specific form of PLE that is powered by commercial off‐the‐shelf automation, fully defined processes, and a formal language of variation based on features. Many case studies show the efficacy of Feature‐based PLE and the improvements in cost, schedule, and quality that can come with it. In this paper, practitioners from four of world's six largest defense companies highlight their experience with the practices that enable and inhibit success with this powerful engineering discipline.